Stock Price Model in Manufacturing Companies - Luqman Hakim; Octojaya Abriyoso; Otto Bustani (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to analyse and answer the phenomenon of Stock Price (SP) with its determinants; Return On Assets (ROA), Dividend Pay-Out Ratio (DPR), Firm Size (SIZE) and Leverage (DER). The model of this study formula is a theoretical framework to find out the factors that influence SP through DER. First model results; ROA has a significant effect on DER. The same results also apply to SIZE, while DPR has no significant effect on DER. The results of the second model; ROA has a significant effect on SP. The same results also apply to SIZE, but they are negatively correlated. The results are different for DER and DPR, both of which have no significant effect on SP so that DER as an intervening variable does not function to mediate SP. The most dominant or sensitive variable in the two research models occurs in ROA. This research can be used as a guide for capital market players in Indonesia to detect what will happen to SP if the variables in this research experience movement. The value of this research is that the SP model formulation via DER is not appropriate for the manufacturing sector.